2007
DOI: 10.1016/j.dsr.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Community structure across a large-scale ocean productivity gradient: Marine bird assemblages of the Southern Indian Ocean

Abstract: International audienceOur objective was to understand how marine birds respond to oceanographic variability across the Southern Indian Ocean using data collected during an 16-day cruise (4-21 January 2003). We quantified concurrent water mass distributions, ocean productivity patterns, and seabird distributions across a heterogeneous pelagic ecosystem from subtropical to sub-Antarctic waters. We surveyed 5155km and sighted 15,606 birds from 51 species, and used these data to investigate how seabirds respond to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 56 publications
2
54
0
Order By: Relevance
“…Elevated abundance of seabirds is found in areas characterized by high production or accumulation of biological matter, such as in frontal areas delineating different water masses (Abrams 1985, Wahl et al 1989, Pakhomov & McQuaid 1996, Hyrenbach et al 2007), along the continental edge (Hay 1992, Piatt et al 2006, or in inshore waters (Harrison et al 1994). On a smaller scale, local interactions between currents and the sea bottom may structure water masses into zones with different properties.…”
Section: Spatial Handicaps Of Preymentioning
confidence: 99%
“…Elevated abundance of seabirds is found in areas characterized by high production or accumulation of biological matter, such as in frontal areas delineating different water masses (Abrams 1985, Wahl et al 1989, Pakhomov & McQuaid 1996, Hyrenbach et al 2007), along the continental edge (Hay 1992, Piatt et al 2006, or in inshore waters (Harrison et al 1994). On a smaller scale, local interactions between currents and the sea bottom may structure water masses into zones with different properties.…”
Section: Spatial Handicaps Of Preymentioning
confidence: 99%
“…mapping, geographic information systems [GIS]) aimed at displaying the data and supporting pertinent hypotheses for further testing (Harrison 1982, Joiris 1991, Hull et al 1997, Ollason et al 1997, (2) Table 2. Contents of the categories that group statistical techniques used to relate seabird distributions and environmental variables 1997, Karnovsky et al 2003, Weichler et al 2004, Hyrenbach et al 2007) and (6) multi-scale approaches (e.g. wavelets, fractal geometry) investigating ecological functional relationships (Russell et al 1992b, Logerwell et al 1998, Mehlum et al 1999, Swartzman & Hunt 2000 that are known to change with scale (Levin 1992).…”
Section: Association Between Seabird Distribution and Environmental Vmentioning
confidence: 99%
“…Relatively little research has been done on the community structure of pelagic marine organisms, most likely due to the difficulty of gathering such data (Venrick 1990). Despite these difficulties, research in pelagic systems has shown clear gradients and structure in the following pelagic communities: marine phytoplankton (Venrick 1982(Venrick , 1990; marine zooplankton (McGowan & Walker 1979, 1985; marine birds (Ballance et al 1997, Woehler et al 2003, Hyrenbach et al 2007; and marine mammals , Baumgartner et al 2001, Hamazaki 2002, Palacios 2003.…”
Section: Introductionmentioning
confidence: 99%